2018
DOI: 10.1029/2018gl079222
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Fates of Petrogenic and Biospheric Carbon in the South China Sea

Abstract: A synthesis of published and newly acquired stable and radiocarbon isotope data from soil, river, and marine particulate organic carbon (OC) from the South China Sea drainage and sedimentary basin reveals that OC derived from bedrock‐erosion (petrogenic OC) and marine productivity comprises the major contributors to bulk OC in particulate matter reaching abyssal depths, while soil‐derived OC appears negligible. Aluminum‐radiocarbon relationships of sediments suggest that soil OC initially associated with detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 61 publications
1
48
0
Order By: Relevance
“…over time series of sinking particles (Blattmann et al, 2018). Therefore, these episodic aged or even petrogenic OM exports, triggered by events such as earthquakes and typhoons, exert large-scale control on radiocarbonscapes in the deep ocean.…”
Section: Event-driven Sedimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…over time series of sinking particles (Blattmann et al, 2018). Therefore, these episodic aged or even petrogenic OM exports, triggered by events such as earthquakes and typhoons, exert large-scale control on radiocarbonscapes in the deep ocean.…”
Section: Event-driven Sedimentationmentioning
confidence: 99%
“…Mineral ballast exerts key control over the sedimentary transport and deposition of OM in aquatic environments (Ittekkot et al, 1990;Wakeham et al, 2009). Investigations have revealed the association of marine OM with lithogenic minerals (Keil et al, 1997;Kennedy and Wagner, 2011), which is also observed in the sinking particles of the South China Sea, which impart a strong effect on 14 C contents of sedimentary OC (Blattmann et al, 2018). The systematic radiocarbonscapes with contrasting modern and ancient forms of sedimentary OM (see insert in Figure 1D), representing marine and petrogenic OM forms, respectively, display strong relationships with mineralogical composition, revealing mineral-specific behavior on the retention and release of terrestrial OM in the marine environment by loss-and-replacement reactions (Figure 1D; Blattmann et al, 2019).…”
Section: Om-mineral Interactionsmentioning
confidence: 99%
“…In order to understand atmospheric chemistry through geologic time, in addition to comprehensively budgeting the effect of mineral chemical weathering (Blattmann et al, 2019a;Hilton et al, 2014), changing reburial efficiency of sedimentary kerogen needs to be evaluated. Direct quantification of kerogen found reburied in sediments is often associated with considerable uncertainty owing to uncertainties in organic matter source apportionment (Blattmann et al, 2019b) and geospatial variability 70 (Blattmann et al, 2018a). While radiocarbon was paramount for establishing the importance of and quantifying kerogen reburial in the Recent (Blattmann et al, 2018b), the utility of radiocarbon quickly diminishes for strata preceding the Last Glacial Maximum owing to its radioactive decay.…”
Section: Tackling Geologic Deep Time 55mentioning
confidence: 99%
“…However, the decay of kerogen on the Earth's surface is incomplete, with physical erosion followed by riverine transport (Galy et al, 2015) and reburial in lacustrine and marine settings (Blattmann et al, 2018a;Blattmann et al, 2019b). The operation of this "simple cycle besides the more complicated common circulation of carbon", enunciated by Sauramo (1938) (Hedges and Oades, 1997), 43 −25 +61 PgC/kyr is currently exported by rivers to oceans (Galy et al, 2015), indicating that the modern day reburial efficiency of this carbon lies in the ballpark of 30% (10-70%).…”
Section: Introductionmentioning
confidence: 99%
“…Due to complex and often temporally varying hydrodynamic conditions, these processes can result in markedly spatial variability in sedimentary OC 14 C in shallow marginal seas (Bao, Blattmann, et al, ). Translocation of sedimentary OM may occur from the shelf to the deep ocean, where it may encounter differing hydrodynamic and depositional regimes (Bao, Strasser, McNichol, et al, ; Blattmann et al, ; Hung et al, ; Hwang et al, ; Oguri et al, ; Zhu et al, ). This complex interplay between source inputs and transport processes renders it challenging to deconvolve underlying carbon cycling, solely based on bulk‐level information (incl., 14 C) on sedimentary OM.…”
Section: Introductionmentioning
confidence: 99%